Use of trajectory and spatiotemporal features for retrieval of videos with a prominent moving foreground object. Issue 2 (February 2016) - Chattopadhyay, Chiranjoy; Das, Sukhendu
Abstract This paper presents generalized spatiotemporal analysis and lookup tool (GESTALT), an unsupervised framework for content-based video retrieval. GESTALT takes a query video and retrieves "similar" videos from the database. Motion and dynamics of appearance (shape) patterns of a prominent moving foreground object are considered as the key components of the video content and captured using corresponding feature descriptors. GESTALT automatically segments the moving foreground object from the given query video shot and estimates the motion trajectory. A graph-based framework is used to explicitly capture the structural and kinematics property of the motion trajectory, while an improved version of an existing spatiotemporal feature descriptor is proposed to model the change in object shape and movement over time. A combined match cost is computed as a convex combination of the two match scores, using these two feature descriptors, which is used to rank-order the retrieved video shots. Effectiveness of GESTALT is shown using extensive experimentation, and comparative study with recent techniques exhibits its superiority.